Perinatal outcome and timing of selective fetal reduction in dichorionic diamniotic twin pregnancies: a single-center retrospective study - Zou, Gang; Ji, Qingfang; Chen, Jianping; Zhang, Luye; Sun, Qianqian; Shi, Yaqi; Yang, Yingjun; Zhou, Fenhe; Wei, Xing; Sun, Luming (Frontiers in Medicine, 2024)
Objective：The aim of this study was to evaluate the pregnancy outcomes of dichorionic diamniotic twin pregnancies that were reduced to singletons at different gestational age.Study Design ： This was a retrospective cohort study of twin pregnancies that underwent fetal reduction to singletons in a single tertiary referral center between 2011 and 2020. A total of 433 cases was included. The cohort was divided into 5 groups according to gestational age at surgery: group A: <16 weeks (125 cases); group B: 16-19 +6 weeks (80 cases); group C: 20-23 +6 weeks (74 cases); group D: 24-26 +6 weeks (48 cases); group E: ≥27 weeks (106 cases). Outcome data was obtained by reviewing the electronic medical records or interviews.Results： Selective reduction was technically successful. Clinical characteristics of population were not different. The overall livebirth rate and survival rate were 96.5% and 95.4%, respectively. Although the rate of spontaneous miscarriage was comparable, gestational age at delivery differed significantly among groups (P<0.001), and there was a trend that gestational age at delivery decreased with the increasing gestational age at surgery in Group A, B, C and D, whereas gestational age at delivery in This is a provisional file, not the final typeset article Group E was later than that in Group D. In Group A, B, C and D, the rates of preterm birth <32 weeks and <34 weeks increased with the increasing gestational age at surgery, while the rates in Group E were significantly lower than that in Group D. Regression analysis showed that timing of reduction may be an independent factor after adjusting for maternal age, parity, pre-pregnancy BMI, ART and cervical length.Conclusions：Selective reduction in experienced hands for a dizygotic abnormal twin is safe and effective. Gestational age at surgery (<26 +6 weeks) was inversely correlated with gestational age at delivery and positively with the rate of preterm birth. Reduction after 27 weeks, where legal, can be performed with a good outcome for the retain fetus.